(3ZfjI CQHGH GdSeGY aj cTa GdbfGY Yf hLhg GdGSJeGYs - (3YHO GdcQje Hf EHQGgje Hf YHO GdcQje GdLjdj GdUhaj , bWH GdOjf,J (B832 (3g` s ((3GdbGgQI s)
(3ChdgG (B:s
(3GdMeO ddg GdPi CbGe ai ebGeGJ GdbQH CbOGe GdQLGd CeG HYO aEfi deG QCjJ bUhQ Gdaghe Yf CWhGQ GdeYGfi s
(3BNQgG (B:s
(3aGdYHhOI YHGQI Yf ebGe gPG GdQLd EPG JfRd ef ebGe GdQHhHjI Edi ebGe GdYHhOjI hHg NJefG GdcJGH hGddg Gdehab s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B50 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B313s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs